Radiative heating and cooling in the middle and lower atmosphere of Venus and responses to atmospheric and spectroscopic parameter variations. (November 2015) - Haus, R.; Kappel, D.; Arnold, G.
Abstract: A sophisticated radiative transfer model that considers absorption, emission, and multiple scattering by gaseous and particulate constituents over the broad spectral range 0.125–1000 µm is applied to calculate radiative fluxes and temperature change rates in the middle and lower atmosphere of Venus (0–100 km). Responses of these quantities to spectroscopic and atmospheric parameter variations are examined in great detail. Spectroscopic parameter studies include the definition of an optimum spectral grid for monochromatic calculations as well as comparisons for different input data with respect to spectral line databases, continuum absorption, line shape factors, and solar irradiance spectra. Atmospheric parameter studies are based on distinct variations of an initial model data set. Analyses of actual variations of the radiative energy budget using atmospheric features that have been recently retrieved from Venus Express data will be subject of a subsequent paper. The calculated cooling (heating) rates are very reliable at altitudes below 95 (85) km with maximum uncertainties of about 0.25 K/day. Heating uncertainties may reach 3–5 K/day at 100 km. Using equivalent Planck radiation as solar insolation source in place of measured spectra is not recommended. Cooling rates strongly respond to variations of atmospheric thermal structure, while heating rates are less sensitive. The influence of mesospheric minor gas variations is small, but may become more important near the cloud base and in case of episodic SO2 boosts. Responses to cloud mode 1 particle abundance changes are weak, but variations of other mode parameters (abundances, cloud top and base altitudes) may significantly alter radiative temperature change rates up to 50% in Venus' lower mesosphere and upper troposphere. A new model for the unknown UV absorber for two altitude domains is proposed. It is not directly linked to cloud particle modes and permits an investigation of radiative effects regardless of the absorbers's chemical composition. A globally averaged Bond albedo of Venus of 0.763 is inferred in accordance with previous results. Considering the gaseous UV absorbers SO2 and CO2 shortward of 0.32 µm, the globally averaged deposited solar net flux at the top of atmosphere (TOA) and the outgoing thermal net flux differ by only 1.5 W m −2 around the mean value of 159 W m −2 for the selected initial atmospheric model. Global radiative equilibrium can be achieved by moderate adjustments of cloud mode and UV absorber abundances. Half of the TOA solar net flux is absorbed by atmospheric constituents at altitudes above 63 km. Consideration of the unknown UV absorber provides about 50% more heating at 68 km compared with a neglect of this opacity source. Less than 5% of the incident flux reaches the surface. There is a broad net cooling region between 70 and 80 km with a strong increase of cooling toward the poles. A net radiative temperature change rate gradient is also observed at 65 km where heating occurs at low latitudes. At altitudes above 80 km, net heating dominates the low and mid latitudes, while net cooling prevails at high latitudes leading to a dominant global average net heating that has to be balanced by dynamical processes to maintain the observed thermal structure. The results of energy balance response analyses will serve as reference for ongoing investigations and provide a profound data base to improve the understanding of radiative forcing of atmospheric dynamical processes. Highlights: A new pure synthetic model for the unknown UV absorber is proposed. Cooling strongly responds to atmospheric parameter changes, heating is less sensitive. Minor gas variations mainly influence cooling near the cloud bottom. Uncertainties due to spectroscopic input data variation are determined. Global average net cooling dominates at 65–85 km and net heating at higher altitudes.